Place of death correlated to socio-demographic factors in a South African hospice - Kraus, Peter A (Department of Public Health and Family Medicine, 2017)
Background: The palliative care literature continually supports the view that home remains the preferred place of death of most patients with terminal illness. However, it also reports that in many countries, palliative care patients sometimes change their minds with regard to this preference. A variety of factors appears to intervene preventing patients from dying at home. The socio-demographics of patients presenting to St. Luke's Hospice, and how this relates to place of death, has never been evaluated. It is believed that in this setting, there is ironically more likelihood of many patients from poorer socio-economic circumstances dying at home. This could be as a result of living with larger families, more difficulty in obtaining access to institutional beds and cultural beliefs. Aim: To determine factors which influence the place of death of patients referred to St. Luke's Hospice over a one-year period. Method: This is a prospective, descriptive, quantitative study of the place of death of new patients referred to St Luke's Hospice, a palliative care service with an inpatient unit and home care programme, between 1 May 2001 and 30 April 2002. Only those patients who died within this time frame were analysed. A "teleform" was designed with the assistance of the Alberta Cancer Board Palliative Care Research Initiative. This form allowed the information to be entered directly into a database for analysis. The variables to be analysed with regard to place of death include: - • Age • Gender • Race • Social Structure • Category of Patient i.e. State or Private • Formal Educational Level • Duration of Illness • Palliative Performance Scale Result This study suggests that. almost two-thirds of patients with a terminal illness can be supported in their homes by a home care programme, without referral to an institution. These statistics correlate well with death statistics of other palliative home care services in industrialised countries. Variables such as age, gender, category of patient, palliative performance scale and duration of illness bore no significant relationship to place of death. However, place of death was strongly associated with race, social structure and socio-economic status. Interestingly, black patients were more likely to die in an institution. Conclusion: Studying socio-demographic factors related to place of death is only one aspect of evaluating and determining the needs of the terminally ill and their families in South Africa. Should or can more people die at home? Are home deaths feasible, and if so how? The task that lies ahead of us in South Africa is to decide what kind of palliative care or other service is optimal. cost effective and appropriate to meet the needs of our multi-cultural society.